Ответы и объяснения

Лучший Ответ!
2013-05-26T16:29:46+00:00

1.) 3x-3y+xy²-x²y=3(x-y)+xy(y-x)=3(x-y)-xy(x-y)=(x-y)(3-xy)

2.) 2a²-2b²-a+b=2(a²-b²)-a+b=2(a-b)(a+b)-(a-b)=(a-b)(2(a+b)-1)

3.) 2x+y+y²-4x²=(2x+y)+(y²-4x²)=(2x+y)+(y-2x)(y+2x)=(2x+y)(y-2x+1)

4.) a³-ab-a²b+a²=a²(a+1)-ab(a+1)=a(a+1)(a-b)

5.) 1-x²+2xy-y²=1-(x²-2xy+y²)=1-(x-y)²=(1-x+y)(1+x-y)

6.) 2x²-20xy+50y²-2=2(x²-10xy+25y²)-2=2((x-5y)²-1)=2(x-5y-1)(x-5y+1)

7.) ac^4-c^4-ac²+c²=ac²(c²-1)-c²(c²-1)=(c²-1)(ac²-c²)=(c-1)(c+1)(a-1)c²

8.) ab²-b²y-ax+xy+b²-x=b²(a+1)-x(a+1)-y(b²-x)=(b²-x)(a+1-y)

2013-05-26T16:41:36+00:00

1.(3х-х²у)+(ху²-3у)=х(3-ху)+у(ху-3)=(ху-3)(х+у)

2.2а²-2b²-a+b=(2a²-2b²)-(a+b)=2(a²-b²)-(A-b)=2(a-b)(a+b)-(a-b)=(a-b)(a+b+2)

 

3.2x+y+y²-4x²=(2x-4x²)+(y+y²)=2x(1-2x)+y(1-y)

4.a³-ab-a²b+a²=(a³-a²b)+(a²-ab)=a²(a-b)+a(a-b)=(a-b)(a²+a)

5.1-x²+2xy-y²=1-(x²-2xy+y²)=1-(x-y)²=1-(x-y)(x-y)